2012
DOI: 10.1007/s10120-011-0128-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the efficacy and safety of chemotherapy with oxaliplatin plus fluorouracil/leucovorin between elderly patients over 65 years and younger patients with advanced gastric cancer

Abstract: Background A chemotherapy regimen with oxaliplatin, fluorouracil, and leucovorin is commonly used to treat advanced gastric cancer (AGC). This study was designed to compare the efficacy and the safety of oxaliplatin plus fluorouracil/leucovorin administered biweekly (mFOL-FOX6) between elderly patients aged over 65 years and younger counterparts with AGC. Methods This analysis included 82 AGC patients (C65:31, \65:51). Patients with previously untreated chemo-naïve advanced adenocarcinoma of the stomach receiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…These studies have shown that elderly patients with cancer with good functional status and without significant co-morbidities may obtain treatment benefits comparable to younger patients [5,6]. However, taking into account that enrolled patients were considered as being eligible for inclusion by the treating physician, these studies should be interpreted with caution because of pre-trial selection bias.…”
Section: Introductionmentioning
confidence: 96%
“…These studies have shown that elderly patients with cancer with good functional status and without significant co-morbidities may obtain treatment benefits comparable to younger patients [5,6]. However, taking into account that enrolled patients were considered as being eligible for inclusion by the treating physician, these studies should be interpreted with caution because of pre-trial selection bias.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast to CRC, the experience of irinotecan‐based chemotherapy in elderly patients is still limited in GC. Some studies indicated that oxaliplatin‐based doublet regimens could also be an option in these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trial data that are available regarding the treatment of elderly patients with AGC is limited and is mostly derived from phase II studies conducted in elderly patients, age subgroup analyses of phase III studies, and retrospective analyses of elderly patient populations. Overall, evidence from these clinical trials suggests that chemotherapy is feasible in elderly patients with AGC [14,[24][25][26][27][28], but elderly patients with AGC are less likely to receive multiple lines of chemotherapy than younger patients [14,15]. For example, studies of first-line chemotherapy in elderly vs younger patients have reported rates of second-line chemotherapy of 38.7% vs 62.7% [14] and 24% vs 68% [15].…”
Section: Clinical Trial Datamentioning
confidence: 99%
“…Because of poor PS, elderly patients and patients with massive ascites may not be considered for a subsequent line(s) of treatment, particularly because these patients have decreased organ function and comorbidities and, therefore, are at greater risk of toxicity and complications [14][15][16][17][18]. Good patient management will likely play an important role in sequential therapy by minimizing the adverse effects of treatment while maximizing the benefits.…”
Section: Introductionmentioning
confidence: 99%